Editorial - Tijen Tunali (Cadernos de Arte Pública)
Art is a defining element of urban culture through creative dynamics that reflect territorially embedded mechanisms but also particular social and cultural processes. Public art presents us with the possibility of unmediated social interaction that leads to  greater access over the production and use of urban public space. Public art’s presence in the urban space is dynamic and interactive that communicates the complex forms of globalization, cultural hybridity, and plurality in contemporary daily life—where we experience politics. Through a multi-disciplinary lens, that combines urban studies, visual studies, sociology, artistic research, art history and political philosophy, this issue maps the contemporary landscape of public art to capture art’s critical place in the reified politics of the urban space. The aim is not to provide an exhaustive description of politics of arts in the public spaces but rather to provisionally reconcile the lack of a dialectical perspective in the critical discursive tools of the scholarship on urban public art.